1992
DOI: 10.1073/pnas.89.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor-operated Ca2+ influx in transfected fibroblast cells is independent of inositol phosphates and release of intracellular Ca2+.

Abstract: Receptor-mediated changes in cytoplasmic calcium concentrations occur either through release from intracellular calcium stores or by the opening of channels in the plasma membrane, allowing influx of calcium from the extracellular fluid. Carbachol, a muscarinic receptor agonist, stimulated both calcium influx and inositol 1,4,5-trisphosphate (InsP3)-mediated intracellular calcium release in A9 fibroblast cells expressing a m3 muscarinic receptor done. The calcium influx persisted even after pretreatment of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…It is well documented that activated M3R initiates both release from intracellular stores and influx across the plasma membrane (Felder et al, 1992;Parekh and Brading, 1992;Carroll and Peralta, 1998). In this study, we experimentally isolated these constituents of Ca 21 entry and found that the Gb5-RGS7 complex inhibits the release pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that activated M3R initiates both release from intracellular stores and influx across the plasma membrane (Felder et al, 1992;Parekh and Brading, 1992;Carroll and Peralta, 1998). In this study, we experimentally isolated these constituents of Ca 21 entry and found that the Gb5-RGS7 complex inhibits the release pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 21 release is mediated by the canonical pathway involving Gq, phospholipase C b (PLCb), and the second messenger inositol triphosphate, and the inhibitory action of Gb5-RGS7 on M3R-stimulated Ca 21 release may be explained by its competition with Gq for the receptor (Blin et al, 1995;Sandiford and Slepak, 2009). Elucidating the role of Gb5-RGS7 in M3R-stimulated Ca 21 influx is more complex as it involves multiple channels that can be expressed and regulated in a cell-and even species-specific manner (Felder et al, 1992;Singer-Lahat et al, 1996;Wuest et al, 2007). We began dissecting this pathway here by using G protein inhibitors and ion channel blockers (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…response, which seems to represent rapid influx of extracellular Ca 2ϩ (peak 1). Ca 2ϩ e influx before, or independent of, Ca 2ϩ i release had been shown to occur upon activation of muscarinic receptors and other GPCRs (Felder et al, 1992;Montero et al, 1994), including MOR in SH-SY5Y cells (Smart et al, 1995). However, a direct experimental demonstration of rapid induction of Ca 2ϩ influx by MOR was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs either by stimulating influx of extracellular Ca 2ϩ e or release of intracellular Ca 2ϩ i stores via soluble second messengers (inositol trisphosphates), or both. Several GPCRs induce rapid Ca 2ϩ influx independent of intracellular Ca 2ϩ release (Felder et al, 1992;Montero et al, 1994). Smart et al (1995) reported that Ca 2ϩ influx preceded intracellular Ca 2ϩ release upon MOR stimulation in human SH-SY5Y neuroblastoma cells shown to express MOR and ␦-opioid receptors (Yu et al, 1986).…”
mentioning
confidence: 99%
“…ET-1 is endogenously present in the CNS including the cerebellum [2,3] and m,-mAChR is the major mAChR subtype expressed in cerebellar granule cells [15,16]. Besides its robust effect in stimulating phosphoinositide hydrolysis [15], m3-mAChR mediates Ca*+ influx independent of inositol phosphates and intracellular Ca*' release [24]. Thus, ETl-induced expression of m,-mAChR protein may result in long-lasting changes in neuronal Ca*+ homeostasis and excitability.…”
Section: Resultsmentioning
confidence: 99%